Berry Phenolic and Volatile Extracts Inhibit Pro-Inflammatory Cytokine Secretion in LPS-Stimulated RAW264.7 Cells through Suppression of NF-κB Signaling Pathway - Inah Gu; Cindi Brownmiller; Nathan B. Stebbins; Andy Mauromoustakos; Luke Howard; Sun-Ok Lee (Antioxidants, 2020)
Berries are a rich source of phytochemicals, especially phenolics well known for protective activity against many chronic diseases. Berries also contain a complex mixture of volatile compounds that are responsible for the unique aromas of berries. However, there is very limited information on the composition and potential health benefits of berry volatiles. In this study, we isolated phenolic and volatile fractions from six common berries and characterized them by HPLC/HPLC-MS and GC/GC-MS, respectively. Berry phenolic and volatile fractions were evaluated for an anti-inflammatory effect using lipopolysaccharide (LPS)-stimulated RAW264.7 macrophage cells by measuring levels of pro-inflammatory cytokines and the nuclear factor-kappa B (NF-κB) signaling pathway. Results showed that LPS-induced excessive production of nitric oxide (NO), prostaglandin E2 (PGE2), cyclooxygenase-2 (COX-2), interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α), which were inhibited by berry phenolic and volatile extracts. Moreover, berry phenolic and volatile extracts reduced the nuclear translocation of NF-κB by blocking the phosphorylation of p65 and degradation of IκBα. These findings showed that berry volatiles from six berries had comparable anti-inflammatory effects to berry phenolics through the suppression of pro-inflammatory mediators and cytokines expression via NF-κB down-regulation, despite being present in the fruit at a lower concentration.